PERSEPSI GURU TERHADAP PENGAMBILAN KEPUTUSAN OLEH KEPALA SEKOLAH DI SMP NEGERI KECAMATAN RAMBATAN KABUPATEN TANAH DATAR - Husni Yanti (Jurnal Bahana Manajemen Pendidikan, 2013)
The goal of this research are to see information about teacher’s perceptions of the decision making by school principal. The population is 112teachers and the sample is 55 people that taken by convenience sampling. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using persentationscore. The result of this research are the Teacher’s Perceptions of the Decision Making by School Principalin the State junior High School Kecamatan Rambatan Kabupaten Tanah Datar stay in good enough category. Kata Kunci : persepsi; pengambilan keputusan